Peningkatan Kemampuan Penalaran Matematis Siswa Menggunakan Pendekatan Pendidikan Matematika Realistik - Indah Lestari; Rully Charitas Indra Prahmana; Wiwik Wiyanti (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2016)
This study aims to determine differences in the average N-Gain mathematical reasoning skills between students who obtain math learning with realistic mathematics education approach and conventional approaches. This research method used is a quasi-experimental with non-equivalent control group design which implemented in one of the 7th private junior high school in Tangerang. The instrument used is a valid test instrument namely pre-test and post-test with descriptive form. The reliability category of this instrument is high. The results showed that there are significant differences in the average N-Gain mathematical reasoning skills between students who take math learning with realistic mathematics education approach and conventional approaches. The average N-Gain mathematical reasoning skills students who receive math learning with realistic mathematics education approach higher than students who receive mathematics learning with conventional approach.